Understanding the Contemporary Social Construction of Sirri Marriages in Indonesia: An Analysis of Islamic Family Law Perspectives - David Wildan; Dini Syamarina (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Research problems and objectives – The phenomenon of sirri marriage or unregistered marriage is still rampant in Indonesia and its legality is still debated. Whereas marriage registration is intended to provide a guarantee of legal certainty for each individual in the family. In practice in the community, sirri marriages are caused by complex factors that form an interesting contemporary social construction to be studied from the perspective of Islamic family law. Purpose and Research methods - This study aims to socially examine the issue of sirri marriage in relation to state legal guarantees and benefits in contemporary Islamic family law. Using a qualitative research method with a normative-sociological approach, this study investigates the causal factors, social and legal implications of sirri marriages from the perspective of Emile Durkheim's Social Theory. Findings - The result of the research is a complex interaction between legal norms and community values in sirri marriage. Sirri marriages in contemporary Islamic family law studies, although often positioned as deviations from formal legal provisions, persist as socially accepted practices within specific cultural and religious contexts. Durkheim's concept of collective consciousness helps explain how societal norms and shared beliefs influence the legitimization of sirri marriages, even in the absence of state recognition. This phenomenon highlights the tension between formal legal frameworks and traditional social practices, underscoring the importance of understanding local values and social structures when addressing issues of legal pluralism. Research recommendations/contributions - This research underscores the need for public education on the importance of marriage registration as a bridge between religious principles and state regulations. The study's contribution lies in offering an integrative perspective that highlights the necessity of harmonizing religious norms with legal recognition to strengthen the protection of family rights within the legal framework of the state. Originality/value - Ultimately, this analysis advocates for a more nuanced and culturally sensitive approach to harmonizing legal regulations with the socio-religious realities of Indonesia's diverse society.